The presence of benzophenone in sunscreens and cosmetics containing the organic UV filter octocrylene: A laboratory study. (13th April 2021) - Foubert, Kenn; Dendooven, Ella; Theunis, Mart; Naessens, Tania; Ivanova, Boryana; Pieters, Luc; Gilissen, Liesbeth; Huygens, Sara; De Borggraeve, Wim; Lambert, Julien; Goossens, An; Aerts, Olivier
Abstract: Background: The reason why patients photosensitized to the drug ketoprofen (KP) may develop severe photoallergic skin reactions to octocrylene (OCT), an organic ultraviolet filter in sunscreens and cosmetics, remains largely unknown. OCT can be synthesized by using unsubstituted benzophenone (BP), a possible human carcinogen. Objectives: To verify if, and to what extent, BP residues are present in OCT‐containing consumer products. Methods: The raw material of OCT and 39 skincare products, of which 28 contain OCT, were chemically analysed for the presence of BP by means of liquid chromatography. Results: In the OCT raw material and in all 28 OCT‐containing products the presence of BP could be demonstrated, mostly in concentrations above 10 ppm (0.001%), whereas a majority of OCT‐free products (8/11, 73%) did not contain BP. Moreover, BP concentrations significantly increased, in a time‐ and temperature‐dependent manner, likely due to the additional degradation of OCT. Conclusions: Photoallergic contact dermatitis from OCT in patients photosensitized to KP might rely on residual BP impurities. Toxicological and ecological studies that evaluate the safety of OCT might also need to consider the concomitant presence of BP.